Challenges and perspectives on functional interpretations of australopith postcrania and the reconstruction of hominin locomotion. Issue 175 (February 2023) - Cazenave, Marine; Kivell, Tracy L.
Abstract: In 1994, Hunt published the 'postural feeding hypothesis'—a seminal paper on the origins of hominin bipedalism—founded on the detailed study of chimpanzee positional behavior and the functional inferences derived from the upper and lower limb morphology of the Australopithecus afarensis A.L. 288-1 partial skeleton. Hunt proposed a model for understanding the potential selective pressures on hominins, made robust, testable predictions based on Au. afarensis functional morphology, and presented a hypothesis that aimed to explain the dual functional signals of the Au. afarensis and, more generally, early hominin postcranium. Here we synthesize what we have learned about Au . afarensis functional morphology and the dual functional signals of two new australopith discoveries with relatively complete skeletons ( Australopithecus sediba and StW 573 ' Australopithecus prometheus '). We follow this with a discussion of three research approaches that have been developed for the purpose of drawing behavioral inferences in early hominins: (1) developments in the study of extant apes as models for understanding hominin origins; (2) novel and continued developments to quantify bipedal gait and locomotor economy in extant primates to infer the locomotor costs from the anatomy of fossil taxa; and (3) novel developments in the study of internal bone structure to extract functional signals from fossil remains. In conclusion of this review, we discuss some of the inherent challenges of the approaches and methodologies adopted to reconstruct the locomotor modes and behavioral repertoires in extinct primate taxa, and notably the assessment of habitual terrestrial bipedalism in early hominins.